2009
DOI: 10.4012/dmj.28.162
|View full text |Cite
|
Sign up to set email alerts
|

.BETA.-tricalcium phosphate and basic fibroblast growth factor combination enhances periodontal regeneration in intrabony defects in dogs

Abstract: The combined effect of β-tricalcium phosphate and basic fibroblast growth factor was observed in the regeneration of periodontal tissue in dogs. For this purpose, either β-TCP and FGF-2 (β-TCP/FGF-2 group) or FGF-2 alone (FGF-2 group) was applied in intrabony defects. The control group received β-TCP alone. The tissues were histologically examined at 2, 4, or 8 weeks following treatment. The control group was characterized by incomplete, newly formed bone around β-TCP particles. The β-TCP/FGF-2 group showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 27 publications
2
36
2
Order By: Relevance
“…The different application methods of bFGF-2 may explain the different types of epithelial repair in this study. These results are similar to the findings in one-wall defects and two-wall defects in dogs following application of the combination of bFGF-2 and β-TCP 15,16) . However, the effect of bFGF-2 on gingival epithelial cells in vivo remains unclear.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The different application methods of bFGF-2 may explain the different types of epithelial repair in this study. These results are similar to the findings in one-wall defects and two-wall defects in dogs following application of the combination of bFGF-2 and β-TCP 15,16) . However, the effect of bFGF-2 on gingival epithelial cells in vivo remains unclear.…”
Section: Discussionsupporting
confidence: 89%
“…(new cementum formation, 80%), who reported similar observations in one-wall defects and two-wall defects in dogs following application of bFGF-2 in conjunction with β-TCP 15,16) . The findings of the present experiment demonstrated that the combination of bFGF-2 and β-TCP failed to interfere with new cementum formation by bFGF-2.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations